Estudio de los métodos de leasing y factoring como apoyo financiero para las Mipymes en Colombia (2017)
This study was carried out in order to provide small and medium-sized entrepreneurs in the construction industry with a guide that allows them to define the financial elements within their company, promoting the growth, development and / or permanence of the company in the market. Taking into account the financial models of leasing and factoring, aimed at education and management in small and medium enterprises, the result of a documentary compilation and the behavior of this field in recent years, found in Internet documents, and the application in financial institutions in Colombia, which contributed to the continuous improvement of construction Mipymes in Colombia, analyzing the advantages, disadvantages, characteristics and restrictions of these products.